Does variation in interpretation of ultrasonograms account for the variation in incidence of germinal matrix/intraventricular haemorrhage between newborn intensive care units in New Zealand?. Issue 6 (21st October 2005) - Harris, D L; Teele, R L; Bloomfield, F H; Harding, J E
Abstract : Background: The incidence of germinal matrix/intraventricular haemorrhage (GM/IVH) reported to the Australian and New Zealand Neonatal Network (ANZNN) varies between neonatal intensive care units (NICUs). Hypothesis: Differences in the capture, storage, and interpretation of the cerebral ultrasound scans may account for some of this variation. Methods: A total of 255 infants with birth weight <1500 g and gestation <32 weeks born between 1997 and 2002 were randomly selected from the ANZNN database, 44 from each of the six NICUs in New Zealand. Twenty two infants from each NICU had cerebral ultrasound scans previously reported to ANZNN as normal; another 22 had scans reported as abnormal. The original scans were copied using digital photography and anonymised and independently read by a panel of three experts using a standardised method of reviewing and reporting. Results: There was considerable variation between NICUs in methods of image capture and quality and completeness of the scans. However, there was little variation in the reporting of scans between the reviewers and the reports to ANZNN (weighted κ 0.75–0.91). Grade 1 GM/IVH was generally over-reported and grade 4 under-reported to the ANZNN. Conclusion: For all NICUs, a high level of agreement was found between the reviewers' reports and the reports to the ANZNN. Thus the variation between NICUs in the incidence of GM/IVH reported to the ANZNN is unlikely to be due to differences in capture, storage, and interpretation of the cerebral ultrasound scans. Further investigation is warranted into the reasons for the variation in incidence of GM/IVH between NICUs.